Improvement of Basal Cell Carcinomas in Patients with Nevoid Basal Cell Carcinoma Syndrome Following by 5-Aminolevulinic Acid Photodynamic Therapy: A Case Report - Chen YJ; Yi Q; Li YM; Li L (Dove Medical Press, 2021)
Yan Jing Chen,* Qin Yi,* Yi Ming Li, Li Li Department of Dermatology and Venereology, West China Hospital, Sichuan University, Chengdu, Sichuan, People's Republic of China*These authors contributed equally to this workCorrespondence: Li LiDepartment of Dermatology and Venereology, West China Hospital, Sichuan University, Guoxue Alley No. 37, Wuhou District, Chengdu, Sichuan, 610041, People's Republic of ChinaTel +86 18980601692Email lilihx_scu@scu.edu.cnAbstract: Nevoid basal cell carcinoma syndrome (NBCCS) is a rare autosomal dominant-inherited disease characterized by multiple basal cell carcinomas, multiple keratocystic odontogenic tumors, palmar and/or plantar pits. A 50-year-old male patient presented to our hospital with multiple plaques and maculopapular lesions on his face and trunk for more than 20 years. A skin biopsy revealed a number of discrete nests of basaloid cells in the dermis where the peripheral cells are arrayed like a palisade. Multiple odontogenic keratocysts and falx cerebri calcification were found. The diagnosis of NBCCS was made. We treated this patient with 5-aminolevulinic acid photodynamic therapy (ALA-PDT) with red light activation, 5% imiquimod cream and surgical excision for the basal cell carcinomas. All the skin lesions on his face improved substantially after eight sessions of red-light ALA-PDT from clinical observation. Red-light ALA-PDT proved to be a good therapeutic method for NBCCS in this case.Keywords: nevoid basal cell carcinoma syndrome, basal cell carcinomas, ALA-PDT, renal cysts